Synergistic Effects of Caffeine in Combination with Conventional Drugs: Perspectives of a Drug That Never Ages - Davide Ialongo; Valeria Tudino; Merve Arpacioglu; Antonella Messore; Elisa Patacchini; Roberta Costi; Roberto Di Santo; Valentina Noemi Madia (MDPI AG, 2023)
Plants have been known since ancient times for their healing properties, being used as preparations against human diseases of different etiologies. More recently, natural products have been studied and characterized, isolating the phytochemicals responsible for their bioactivity. Most certainly, there are currently numerous active compounds extracted from plants and used as drugs, dietary supplements, or sources of bioactive molecules that are useful in modern drug discovery. Furthermore, phytotherapeutics can modulate the clinical effects of co-administered conventional drugs. In the last few decades, the interest has increased even more in studying the positive synergistic effects between plant-derived bioactives and conventional drugs. Indeed, synergism is a process where multiple compounds act together to exert a merged effect that is greater than that of each of them summed together. The synergistic effects between phytotherapeutics and conventional drugs have been described in different therapeutic areas, and many drugs are based on synergistic interactions with plant derivatives. Among them, caffeine has shown positive synergistic effects with different conventional drugs. Indeed, in addition to their multiple pharmacological activities, a growing body of evidence highlights the synergistic effects of caffeine with different conventional drugs in various therapeutic fields. This review aims to provide an overview of the synergistic therapeutic effects of caffeine and conventional drugs, summarizing the progress reported to date.